Tropical peat soil changes across successive oil palm generations in Sarawak, Malaysia - Ratai, Jicqueline; Teh, Christopher Boon Sung; Tan, Ngai Paing; Mohidin, Hasmah; Goh, Kah Joo; Sangok, Faustina Elfrida; Melling, Lulie (Elsevier Ltd, 2024)
Oil palm is commonly replanted once reaching the end of its productive lifespan. This cyclical planting practice in oil palm plantations could have long-term implications for the humification and properties of tropical peat soil. This study aimed to investigate the changes observed across successive generations of oil palm plantations in Sarawak, Malaysia. Fourier Transform Infrared Spectroscopy (FTIR) was applied to examine the quality of the Soil Organic Matter (SOM), specifically the functional groups, humification index, Hydrophobicity Index (HI), and Degree of Degradation (DDI). Overall, the peat humification trend was in the order of 2nd Gen > Forest >1st Gen. The higher presence of recalcitrant compounds of lignin in the soil was attributed to the higher HI and lower DDI in the 2nd Gen. The relationship between the Pyrophosphate Solubility Index (PSI) and the humification index further revealed a significant increase in the relative abundance of humic substances with the maturity of degraded organic matter. These findings suggest a notable transition, implicating a shift towards a more stable form of SOM over the long-term utilization of tropical peatland for oil palm plantations. This is characterised by a significant increase in the relative abundance of aromatic, phenolic, and carboxylic functional groups. The study also highlights the need for further research on the linkage between these changes and greenhouse gas emissions to enhance our understanding of the long-term biogeochemical cycle of oil palm on tropical peatlands.